Pemberdayaan Peternak Perempuan Melalui Transfer Teknologi Pakan Komplit - Sukarne Sukarne; Muhammad Nursan; Dahlanuddin Dahlanuddin; Aeko Fria Utama FR; Tarmizi Tarmizi (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Feed is still a major problem in the development of the livestock sub-sector. So far, farmers are still relying on animal feed needs from natural grass which causes low livestock productivity and limited livestock rearing capacity. To overcome these problems, the purpose of this community service activity is to provide training and assistance to female breeders to make complete feed and implement the use of complete feed for livestock. This training activity was carried out in Wanasaba Lauk Village, East Lombok Regency. Participants in the training activity were 15 female breeders under the Ridho Ilahi Center for Animal Husbandry. The method used in this study is the delivery of materials and the practice of making complete feeds. The training activity was carried out for 2 days and assistance for the application of complete feed technology was carried out for 3 months. The result of this training is that female farmers gain knowledge and skills in producing complete feed and in terms of capacity calculations, breeders are able to maintain a minimum of 5 heads of livestock which previously was only a maximum of 2 heads. Then in terms of productivity, average daily gain (ADG) of livestock reached 0.42 Kg/day.